(untitled) (The Pakistan Development Review, 2004)
Like many developing economies, the South Asian countries are opening-up their economies with a view to accelerating their economic growth through greater trade and investment. In this context, attempts have also been made to encourage regional trade under the aegis of the South Asian Association for Regional Cooperation (SAARC). In particular, the South Asian Preferential Trade Agreement (SAPTA) provides for reductions in tariffs and other restrictions on specific commodities on a reciprocal basis, and the eventual objective is to integrate the South Asian economies into a free trade area through SAFTA, which would come into force on January 1, 2006. However, despite greater attention on regional economic cooperation initiatives, there has been little progress in regional trade expansion: intra-regional trade continues to be minimal, not exceeding 5 percent of the total trade of the South Asian economies. This paper highlights the importance of regional economic integration in South Asia as elsewhere, spells out the factors which have so far hampered economic cooperation in the region, and outlines a future course of action to achieve greater economic integration in South Asia. Section 2 provides a broad perspective on regional economic integration with a particular focus on the need to foster greater economic cooperation in South Asia. Section 3 discusses the factors that have impeded intra-regional trade and economic ties within the region. Section 4 spells out measures to enhance economic cooperation in the SAARC region, while Section 5 concludes the discussion.